Sex differences in atrial remodeling and its relationship with myocardial fibrosis in hypertrophic obstructive cardiomyopathy - Bi, Xuanye; Song, Yanyan; Yang, Chengzhi; Song, Yunhu; Zhao, Shihua; Qiao, Shubin; Zhang, Jinying (Frontiers in Cardiovascular Medicine, 2022)
Background This study aimed to explore the effect of sex on left atrial (LA) remodeling and its relationship with myocardial fibrosis in patients with hypertrophic obstructive cardiomyopathy (HOCM). Methods and results A total of 85 patients with HOCM were enrolled. Myocardial fibrosis was quantified by the collagen volume fraction (CVF) in myocardial samples. The early atrial peak of emptying rate (PER-E) was assessed by LA volume/time (V/t) curves derived from cardiac magnetic resonance (CMR) imaging analysis. The PER-E index was PER-E normalized by left ventricular (LV) filling volume. Patients with HOCM showed a lower PER-E index than healthy controls (P = 0.027). Compared with men, the PER-E (P < 0.001) and the PER-E indexes (P = 0.012) in women were lower. In CVF-stratified subgroups, a sex difference in the PER-E index was eliminated (P > 0.05). The CVF was correlated with the PER-E and PER-E indexes in both sexes (all P-values were <0.05). In multivariate regression analysis, sex (P = 0.007) and CVF (P < 0.001) were independently correlated with PER-E (all P-values were <0.05). Conclusion Patients with HOCM presented LA reverse remodeling. Impaired LA function was more common in female patients with HOCM due to their susceptibility to myocardial fibrosis.